Körperkoordinations test für Kinder: A short form is not fully satisfactory - Biino, Valentina; Giustino, Valerio; Guidetti, Laura; Lanza, Massimo; Gallotta, Maria Chiara; Baldari, Carlo; Battaglia, Giuseppe; Palma, Antonio; Bellafiore, Marianna; Giuriato, Matteo; Schena, Federico (Frontiers in Education, 2022)
Assessment of motor competence (MC) is crucial to finding deficiencies in children's motor development. Because of the need to ensure validity, reliability, and feasibility, the selection of contemporary testing batteries is a difficult task. Many papers report the validity of the KTK test in describing MC in school aged children. KTK consists of 4 four separate items: walking back, jumping sideways, moving sideways, and hopping for height. Some authors suggested the use of a short version of KTK that includes 3 items excluding one subtest: hopping for height. This study aimed to evaluate the effectiveness of short versions of Körperkoordinationstest für Kinder (KTK). A sample of 2,231 participants (boys: n=1,188; girls: n = 1,043; age range: 6–12 years) were recruited from Italian schools between January 2019 and February 2020 and they performed the complete version of KTK. Stepwise linear regression was performed on the dataset to evaluate the ideal number of variables to describe the KTK short form version. Data for both the sexes and all ages indicated that considering the item combinations of each short version, the highest R squares were obtained in those that included exactly the deleted subtest (ranging from 0.881–0.979). The adoption of a short form does not seem to provide a fully satisfactory condition for measuring MC in children 6–12 years.